2016
DOI: 10.1177/0145561316095004-506
|View full text |Cite
|
Sign up to set email alerts
|

Is Unenhanced 18F-FDG–PET/CT Better than Enhanced CT in the Detection of Retropharyngeal Lymph node Metastasis in Nasopharyngeal Carcinoma?

Abstract: Positron-emission tomography/computed tomography (PET/CT) has been proposed as a means to enhance the pretreatment evaluation of cervical lymph node status in patients with nasopharyngeal carcinoma (NPC). We conducted a prospective study to compare PET/CT and enhanced CT for the detection of retropharyngeal lymph node (RLN) metastasis in NPC, and to ascertain the factors that affect its diagnostic performance. Our study population was made up of 33 patients—24 men and 9 women, aged 30 to 81 years (mean: 52)—wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Most authors agreed the criterion of LRPNs selected the MIAD ranging from ≥ 5 to ≥ 6 mm in the past two more decades [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. As a single parameter, MIAD was proved to be more useful than the maximal axial diameter by Zhang's study [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most authors agreed the criterion of LRPNs selected the MIAD ranging from ≥ 5 to ≥ 6 mm in the past two more decades [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. As a single parameter, MIAD was proved to be more useful than the maximal axial diameter by Zhang's study [13].…”
Section: Discussionmentioning
confidence: 99%
“…Based on control subject analysis, Lam and King used minimal axial diameter (MIAD) of 4 and 5 mm as the upper limit of normal LRPNs [2,3]. A diameter of 5 mm or higher as a criterion of malignancy was widely indicated by previous studies [4][5][6][7][8][9][10][11][12]. However, Zhang et al reported that ≥6 mm diameter might be a better cutoff point for malignancy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Various imaging technologies, such as CT, MRI, and 18 F-FDG, have been widely used in the evaluation of head neck cancer ( 6 , 7 ). MRI has a higher ability in the presentation of soft tissue than CT or PET, especially in the evaluation of primary tumors, since the tumor may extend to the mucous membrane alone.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been few published data on prevalence of RPLN involvement in patients with nonnasopharyngeal head and neck cancer and the frequency of positive retropharyngeal nodes reported in HPC varies hugely, ranging from 10% to 62% (10-12). These highly discrepant findings across different reports were mainly ascribed to two reasons, one being that most studies included other head and neck carcinomas and had small sample sizes, and were not limited to HPC; another reason being that various imaging technologies, such as CT, MRI and (18)F-FDG PET had been used (5,13). Actually, MRI has been shown to be superior to CT images for detecting metastatic RPLNs; MRI is considered the preferred method for assessing metastatic RPLNs, as a guide to physicians prescribing appropriate treatment (14).…”
Section: Discussionmentioning
confidence: 99%